2014
DOI: 10.1186/1756-0500-7-139
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the association between gestational diabetes mellitus and chronic hepatitis B infection during pregnancy

Abstract: BackgroundChronic hepatitis B (CHB) infection during pregnancy is associated with insulin resistance. A meta-analytic technique was used to quantify the evidence of an association between CHB infection and the risk of gestational diabetes (GDM) among pregnant women.MethodsWe searched PubMed for studies up to September 5th 2013. Additional studies were obtained from other sources. We selected studies using a cohort-study design and reported a quantitative association between CHB infection during pregnancy and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The results of previous studies on the association between the HBsAg carrier status and subsequent risk of HDP, GDM and preterm birth were conflicting. Although several previous studies suggested that HBsAg carrier status is associated with the risk of HDP, GDM and preterm birth, other studies did not . This inconsistency may also be explained by differences in race, HBV endemic areas, diagnostic criteria and the confounding variables included in their analyses.…”
Section: Discussionmentioning
confidence: 86%
“…The results of previous studies on the association between the HBsAg carrier status and subsequent risk of HDP, GDM and preterm birth were conflicting. Although several previous studies suggested that HBsAg carrier status is associated with the risk of HDP, GDM and preterm birth, other studies did not . This inconsistency may also be explained by differences in race, HBV endemic areas, diagnostic criteria and the confounding variables included in their analyses.…”
Section: Discussionmentioning
confidence: 86%
“…Our study finding was in contrast to the previous meta-analysis addressing the same question, which, however, showed no significant association. 16 This study searched the literature up to The study sample represents the population of interest on key characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HBV infection thus might have an impact on glucose homoeostasis and insulin resistance. Several studies investigated the association between HBsAg positivity during pregnancy and GDM . Nevertheless, the findings are conflicting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the association between chronic hepatitis B infection and the risk of DM and/or GDM remains less convincing. Moreover, according to a recent meta-analysis, it was concluded that gestational diabetes mellitus is not attributable to CHB infection during pregnancy [43]. According to literature HBV can be a risk factor for diabetes mellitus and our finding could imply that the pregnant women positive for HBsAg are at a higher risk of developing gestational diabetes mellitus [17,18].…”
Section: Discussionmentioning
confidence: 59%